(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
In his poetic work, Sheikhzada mainly wrote on modern topics, while in his dramaturgy he plunged deeply into the historical past, giving new artistic life to figures and events that helped to highlight modern problems in it. One of the outstanding figures of Uzbek literature, the famous poet, playwright, literary critic and translator Maksud Shaikhzada stood out among all of us not only in terms of mind, but also in terms of figure. Mukhtar-agha’s clumsy question did not seem to melt away to him.